Interdisciplinary qualitative research in global development : a concise guide - Haenssgen, Marco Johannes, 1986- (Emerald points., 2019)
Interdisciplinary Qualitative Research in Global Developmentprovides a sorely needed practical introduction to the interdisciplinary and increasingly complex field of global development research, and it does so in a concise format can easily be taken into the field.